Kualitas Layanan ATM Bank NTB Syariah dalam Rangka Meningkatkan Kepuasan Nasabah - Abdul Hafith; Muhammad Saleh; Rudi Masniadi (Indonesian Journal of Social Sciences and Humanities, 2020)
Empirical facts show that every bank has made improvements in service quality, both related to customer risk guarantees, as well as service conveniences and features to create customer convenience. One of the efforts made by banks in order to optimize services is the availability of Automated Teller Machines (ATMs). The purpose of this study was to determine the strategy for improving ATM services in order to increase the satisfaction of customers at NTB Syariah Bank by taking the study area at the Bima Soekarno Hatta Branch Office (BO). This research use descriptive-qualitative approach. This research data collection method uses interviews with research informants from the service provider side, in this case, Bank NTB Syariah KC Bima Soekarno Hatta and service users (customers, entrepreneurs, BPKAD Bima City & District and other stakeholders). The analytical tool used with qualitative analysis with data validity test using triangulation. The results showed the strategy of NTB Syariah Bank Bima Soekarno Hatta BO in the five dimensions of services, including: tangible, reliability, responsiveness, assurance and empathy have a positive effect on customer satisfaction of ATM users.